Nurk : the strange, surprising adventures of a (somewhat) brave shrew - Vernon, Ursula (Orlando, Fla. : Harcourt, 2008)
Nurk, a sort-of brave shrew, packs up a few pairs of clean socks and sails off on an accidental adventure, guided by wisdom found in the journal of his famously brave and fierce grandmother.
5.9
3-6.
3-6
Keywords: Courage -- Juvenile fiction; Diaries -- Juvenile fiction; Dragonflies -- Juvenile fiction; Letters -- Juvenile fiction; Shrews -- Juvenile fiction; Adventure and adventurers -- Fiction; Courage -- Fiction; Diaries -- Fiction; Dragonflies -- Fiction; Letters -- Fiction; Shrews -- Fiction; Adventure fiction; Courage -- Fiction; Diaries -- Fiction; Dragonflies -- Fiction; Letters -- Fiction; Shrews -- Fiction; Adventure fiction